ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA MATA UANG DIGITAL BITCOIN - Dede Putra; Muhammad Kadafi; Nanok Fitriyadi (Tinta Nusantara 2018 Vol.1, 2022)
This study aims to determine the factors that affect Bitcoin prices during the period December 3, 2018 – December 1, 2020. The results show that: (1) Total Bitcoin has a negative effect on Bitcoin prices in the long and short term; (2) The number of transactions, fees per transaction, (3) Total Bitcoin, number of transactions, and fees per transaction, together have a significant effect on the Bitcoin price by 19.67% in the long term and by 7.26% in the long run. short; (5) Error Correction Term (ECT) shows the short-term to long-term balance adjustment within a period of 9 to 10 days.